Innovation of Tourism Supply Chain Management: A New Agenda for Optimization. The Case of Kazakhstan - TUKIBAYEVA, Kuralay; ZHANSEITOVA, Gulnara; KIRDASINOVA, Kasiya; PRANEVICH, Alla; SULEIMENOVA, Zhanargul; TURALIN, Amirzhan; NURGALIYEVA, Almagul (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
Despite the recognition of tourism as a priority sector, the development pace and indicators remain low. Innovation management methods are required that will positively affect the entire industry. The main article goal is to identify the problems of tourism sector development for the positive effects achievement and the system transition to a new, qualitative one, as well as identifying barriers and constraints. The problems raised by the authors in the article require comprehensive study and analysis. The authors conducted a comparative analysis of travel and tourism competitiveness index of the Republic of Kazakhstan for 2017 and 2019 years. The authors also analyzed the main indicators of the development of the tourism sector, financial and economic activities of tourism companies in the Republic of Kazakhstan, studied the tourism potential of Nur-Sultan city and Akmola region. As a result of the conducted research, conclusions are drawn, and recommendations are given.